The Romanticization of Mental Illness and Adolescent Identity Formation: Marina and the Diamond's Electra Heart. Issue 1 (31st December 2023) - Shankar, Shravanti
ABSTRACT: Marina and the Diamonds' album, Electra Heart (2012), by glamorizing suffering, provides adolescents an avenue to find solidarity with others who are self-critical and depressed. Adolescents of the 2010s have formed their identities by crowdsourcing on the internet in response to this album. The character of Electra Heart represents a modern-day negative ego ideal for adolescents. Idealization of her character fans the flames of narcissistic destructive behavior in adolescents, but also provides a way for adolescent girls to symbolize and express negative feelings without acting on them.